Cripping the deadline: disrupting academic ableism and industrial time in journalism pedagogy - Ntibinyane, Ntibinyane Alvin (My University, 2026)
Journalism education is anchored to rigid deadlines that are routinely framed as neutral markers of professionalism, rigour, and readiness for industry practice. This article argues that such temporal norms function instead as ableist disciplinary technologies that privilege speed, endurance, and bodily consistency while excluding students whose bodyminds operate outside industrial time. Bringing journalism studies into conversation with critical disability studies (CDS) and crip theory, this article reframes the deadline as a pedagogical choice rather than an inevitable professional necessity. This paper does not argue for the abandonment of deadlines, but for a broader understanding of journalistic competence that values temporal coordination, collaborative newsroom labour, ethical reflection, and access. Drawing on concepts of crip time, fluidity, and interdependence, it critiques transaction-based accommodation models and offers a structural reimagining of newsroom pedagogy. Through concrete strategies, including rolling deadlines, slow journalism approaches, and tiered participation, the article operationalizes temporal justice within production-based courses. By dismantling the “lone wolf” reporter myth and centring care-based collective intelligence, the article proposes a framework for liberatory access that deepens ethical practice and redefines journalistic competence beyond the limits of endurance and immediacy.
Keywords: journalism pedagogy; academic ableism; crip theory; crip time; deadlines; newsroom simulations